Complexity and crisis call for shared leadership and empowered teams - Çırpan, Hüseyin (Springer International Publishing Ag, 2017)
It is a very well-known fact that firms are operating in a very volatile business environment. The success and failure of every type of organisation mainly depends on the quality of leadership, and the complexity of today's business environment makes leadership increasingly challenging. Many crisis management mistakes have been attributed to leadership failures. It is becoming almost impossible for any individual to possess all of the skills and abilities needed to competently navigate organisations through today's challenges. Complexity and crisis by their very nature call for looking at the leadership role from a new perspective and responding to the new reality differently to sustain a business. Here, we will first explore the nature of complexity and crisis. By doing that, we illustrate the requirements of those situations in terms of leadership, and we move on to explain the concept of shared leadership and what is needed to apply it effectively. Since business culture is of vital importance in the effective application of shared leadership, we will delineate how leaders can create a culture that fosters empowerment for teams.
WOS: 000415645900013
Keywords: Complexity; Leadership; Empowered Teams